Answer:
<u>18.8%</u>
Step-by-step explanation:
For calculating this, focus on one part of the table :
- The row where students do not like sandwiches
There are 32 students who do not like sandwiches, and 6 of them do not like pies. Take this a proportion :
- P (does not like pies, do not like sandwiches) = 6/32
- P = 3/16
- P = <u>18.8%</u>
Answer:
Solve for
x
x
by simplifying both sides of the equation, then isolating the variable.
x
≈
0.25181781
Step-by-step explanation:
Answer:
This is a geometric sequence since there is a common ratio between each term. In this case, multiplying the previous term in the sequence by
2.1
gives the next term. In other words,
a
n
=
a
1
⋅
r
n
−
1
.
Geometric Sequence:
r
=
2.1
This is the form of a geometric sequence.
a
n
=
a
1
r
n
−
1
Substitute in the values of
a
1
=
5
and
r
=
2.1
.
a
n
=
(
5
)
⋅
(
2.1
)
n
−
1
Remove parentheses around
2.1
.
a
n
=
5
⋅
2.1
n
−
1
Step-by-step explanation:
![\mathfrak{\huge{\pink{\underline{\underline{AnSwEr:-}}}}}](https://tex.z-dn.net/?f=%5Cmathfrak%7B%5Chuge%7B%5Cpink%7B%5Cunderline%7B%5Cunderline%7BAnSwEr%3A-%7D%7D%7D%7D%7D)
Actually Welcome to the Concept of the Inverse of real function.
Let's consider here, g(n) = y ,
so we get as,
![y = \sqrt[3]{ \frac{n - 1}{2} }](https://tex.z-dn.net/?f=y%20%3D%20%20%5Csqrt%5B3%5D%7B%20%5Cfrac%7Bn%20-%201%7D%7B2%7D%20%7D%20)
no, cubing the power both side we get as,
=>
![{y}^{3} = \frac{n - 1}{2}](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B3%7D%20%20%3D%20%20%5Cfrac%7Bn%20-%201%7D%7B2%7D%20)
now,
![2 {y}^{3} = n - 1](https://tex.z-dn.net/?f=2%20%7By%7D%5E%7B3%7D%20%20%3D%20n%20-%201)
so finally, we get as,
=>
![n = 2 {y}^{3} + 1](https://tex.z-dn.net/?f=n%20%3D%202%20%7By%7D%5E%7B3%7D%20%20%2B%201)
hence,here, n = inverse of the g(n) function.
so,
g^-1 (n) = 2y^3+1.